Melanogenic Effects of Maclurin Are Mediated through the Activation of cAMP/PKA/CREB and p38 MAPK/CREB Signaling Pathways. (23rd December 2019) - Hwang, Young Sun; Oh, Sae Woong; Park, See-Hyoung; Lee, Jienny; Yoo, Ju Ah.; Kwon, Kitae; Park, Se Jung; Kim, Jangsoon; Yu, Eunbi; Cho, Jae Youl; Lee, Jongsung
Abstract : Melanogenesis is the biological process which the skin pigment melanin is synthesized to protect the skin against ultraviolet irradiation and other external stresses. Abnormal biology of melanocytes is closely associated with depigmented skin disorders such as vitiligo. In this study, we examined the effects of maclurin on melanogenesis and cytoprotection. Maclurin enhanced cellular tyrosinase activity as well as cellular melanin levels. We found that maclurin treatment increased the expression of microphthalmia-associated transcription factor (MITF), tyrosinase-related protein- (TRP-) 1, TRP-2, and tyrosinase. Mechanistically, maclurin promoted melanogenesis through cyclic adenosine monophosphate (cAMP) response element binding (CREB) protein-dependent upregulation of MITF. CREB activation was found to be mediated by p38 mitogen-activated protein kinase (MAPK) or cAMP-protein kinase A (PKA) signaling. In addition, maclurin-induced CREB phosphorylation was mediated through the activation of both the cAMP/PKA and the p38 MAPK signaling pathways. Maclurin-induced suppression of p44/42 MAPK activation also contributed to its melanogenic activity. Furthermore, maclurin showed protective effects against H2 O2 treatment and UVB irradiation in human melanocytes. These findings indicate that the melanogenic effects of maclurin depend on increased MITF gene expression, which is mediated by the activation of both p38 MAPK/CREB and cAMP/PKA/CREB signaling. Our results thus suggest that maclurin could be useful as a protective agent against hypopigmented skin disorders.